MAKSIM KUANTITAS DAN MAKSIM RELEVANSI PADA YOUTUBE NAJWA SHIHAB: 20 TAHUN TIMOR LESTE CERITA SETELAH MERDEKA - Humairoh, Siti (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The existence of basic principles in communicating in pragmatics can be referred to as the principle of cooperation. The principle of cooperation according to Grice, namely the maxim of quantity, maxim of quality, maxim of relevance, and maxim of implementation. This study examines the maxim of quantity and maxim of relevance more. The purpose of this study is to explain the maxim of quantity and the maxim of relevance that exist on Najwa Shihab's YouTube about 20 Years of Timor Leste, Stories After Independence. This research method uses descriptive qualitative and note-taking techniques to collect data. The results of the study state that there are 11 maxims of quantity and maxims of relevance in the video. Of the 11 maxims, there are 6 maxims of quantity and 5 maxims of relevance. The maxim of quantity can be seen that what the speaker answers is in accordance with the purpose and is not exaggerated, while the maxim of relevance answers with relevance and what is being questioned is in accordance with 5w+1h.